(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Economic Botany means utilization of those plants that have some useful application so much so that it results in financial or monetary gains. Use of plants for various reasons is an age old practice and dates back to start of life on earth. The first living cells called as prokaryotes were the ones that thrived on chemical energy which they derived from mineral reserves of the earth. With the appearance of first photosynthesizing bacteria i.e., BGA, rest all other organisms began to be dependent on kingdom plantae either directly or indirectly. This trend continued throughout evolution of various life forms. When human beings evolved then slowly they started realizing the importance of various plant forms either as food, for shelter, medicines etc. Different scientists have different opinions about beginning of cultivation on earth. However, cultivation can be roughly dated back to 7000 to 10,000 years ago. In those times only the plants whose usefulness was established were cultivated.